PERILAKU DAN LAJU SERANGAN PENGGEREK KAYU DI LAUT PADA KAYU TUSAM (PINUS MERKUSII JUNGH. et de Vr.) - Mohammad Muslich (Jurnal Penelitian Hasil Hutan, 1989)
This study   is intended   to recognize  the  behaviour  and  infestation   rate  of  marine  borers. Forty  samples  of pine  wood,  measuring  120  cm  x  5 cm x 5 cm,. vertically  floated  at Ram but Island seashore.  These samples  are divided   in  to  three  section:    top,  midle  and  bottom.    The observation   were carried out  after  1,  2,  3 and  6 months    by  splitting   the  sample.The results  showed  that  the  infestation   started  from  the bottom   upwards.  The length  and diameter  of the burrow  is controlled    to  a  certain  extent    by  the  intensity   of  the  borer population    in  the  wood.   When crowded,   the  borer  may grow  only  a few  cm.   After six  months   of  experiment,    the  infestation   rate of  samples  showed   the following   regression equation;  i.e,  top section  Y 1=   0, 134 (X)2,375,   milde section   Y2= 2,569  (X)1,113   and bottom  section  Y 3=  3,334  (X)0,142.